Liquidity, Cash Flow, and Firm Size as Determinants of Financial Distress: Evidence from Indonesian Industrial Sector Companies - Yas'aa Athalia; Indradi, Donny (Yayasan Pendidikan Penelitian Dan Pengabdian Al-amsi, 2025)
This study examines the effect of liquidity, cash flow, and firm size on financial distress in industrial sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This study employs a quantitative approach using secondary data obtained from annual financial reports. The sample consists of 19 companies selected through purposive sampling, resulting in 95 panel data observations. Panel data regression analysis was conducted using EViews 12. The results indicate that liquidity, cash flow, and firm size simultaneously affect financial distress. Partially, liquidity and firm size have a significant effect on financial distress, while cash flow shows no significant effect. These findings suggest that a company’s ability to manage short-term obligations and asset size plays an important role in determining financial distress conditions. This study provides implications for management and investors in assessing early warning signals of financial distress.